Historiography of Brazilian education: training and development field of the history of education in Brazil - Saviani, Dermeval (Acta Scientiarum. Education, 2015)
This paper is about the historiography of the Brazilian education starting with the consideration about the appearance and development of the field of history of education in Brazil covering five aspects: 1) preservation of the memory of the Brazilian education; 2) introduction of the subject History of Education in the curricula of the common schools and in the courses of pedagogy; 3) historiographic production about education; 4) organization of research groups in the history of education; 5) circulation of the production of the field of the history of Brazilian education covering the different forms of publicity consubstantiated in the different types of events and in the different types of publications in the area of history of education. Then, there is the consideration of the course of the historiography in the Brazilian education as a process of construction-deconstruction of the educational memory. Finally, in the last part, there is the critical appreciation of the historiography of the Brazilian education in the current situation.